FACTORS THAT INFLUENCE TRADERS' DECISION MAKING IN PAYING TRADE ZAKAT IN WEST JAVA - Huda, Inna Rotul; Alhifni, Anas (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This research aims to determine the factors that influence traders' decision-making in paying trade zakat in West Java. The sampling technique was carried out using a purposive sampling method. The total sample obtained was 97 respondents from Muslim traders in West Java who paid zakat proceeds from their merchandise to zakat management institutions. The analysis technique used is a factor analysis technique. There are 2 factors that influence traders in making decisions to pay zakat, namely Factors that Form Traders' Decisions. which consists of knowledge, religiosity, service quality and the role of government. Next are the Trader Behavior Factors which consist of the environment and the trader's attitude.